Effect of Dynamic Elastomeric Fabric Orthoses on Postural Control in Children With Cerebral Palsy. Issue 4 (2015) - Bahramizadeh, Mahmood; Rassafiani, Mehdi; Aminian, Gholamreza; Rashedi, Vahid; Farmani, Farzad; Mirbagheri, Sedigheh Sadat
Abstract : Purpose: The aim of this study was to evaluate the effect of dynamic elastomeric fabric orthoses (DEFOs) on postural control in children with cerebral palsy (CP). Methods: Ten children with spastic diplegic CP and 10 children with typical development participated. Knee extension was measured using electrogoniometry. The standard deviation of excursion and phase plane portraits of velocity in the anteroposterior and mediolateral directions were calculated from force platform signals as center of pressure parameters with or without a DEFO. Results: Maximum standing knee extension for children with CP improved after 6 weeks of wearing DEFOs ( P < .05). Center of pressure parameters did not improve when comparing pre- to 6 weeks post-DEFO use ( P < .05). Conclusion: The DEFO can reduce the crouch position without any negative effect on postural stability in children with CP. However, postural control does not improve in a 6-week timeframe. Abstract : The authors found increased knee extension in standing after 6 weeks of wearing the elastic orthotic with no negative or positive effects on postural control.